Perancangan Dan Implementasi Sistem Informasi Rekam Medis (Studi Kasus: Puskesmas Onekore) - Andy Ahmad; Ferdinandus Lidang Witi (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2021)
The medical record information system is an information system that manages patient data and documents containing patient identities, examination results, payments and other services that have been provided to patients. The existing medical record information system at the Onekore Health Center is still processed manually, namely using a ledger for recording and also takes up a lot of storage space. So that patient service at the Onekore Health Center becomes less effective and efficient. Therefore, we need a concept for processing patient medical record data by considering the time efficiency and safety required for the patient data collection process. The purpose of this study is to build a computerized medical record information system in order to provide convenience for medical officers in providing health services to patients to be more effective and also easier in making reports. This medical record information system is designed using the Microsoft Visual Studio programming language and MySQL as the database. The research method used in this research is descriptive qualitative method. While the testing technique uses the Blackbox testing method.